3D navigated implantation of the glenoid component in reversed shoulder arthroplasty. Feasibility and results in an anatomic study. Issue 4 (3rd July 2013) - Stübig, Timo; Petri, Maximilian; Zeckey, Christian; Hawi, Nael; Krettek, Christian; Citak, Musa; Meller, Rupert
Abstract Background Reversed shoulder arthroplasty is an alternative to total shoulder arthroplasty for various indications. The long‐term results depend on stable bone fixation, and correct positioning of the glenoid component. The potential contribution of image guidance for reversed shoulder arthroplasty procedures was tested in vitro. Material and Methods 27 positioning procedures (15 navigated, 12 non‐navigated) of the glenoid baseplate in reverse shoulder arthroplasty were performed by a single experienced orthopaedic surgeon. A Kirschner wire was placed freehand or with the use of a navigated drill guide. For the navigated procedures, a flat detector 3D C‐arm with navigation system was used. The Kirschner wire was to be inserted 12 mm from the inferior glenoid, with an inferior tilt of 10° and centrally in the axial scapular axis. The insertion point in the glenoid as well as the position of the K‐wire in the axial and sagittal planes were measured. For statistical analysis, t‐tests were performed with a significance level of 0.05. Results The inferior glenoid drilling distance was 14.1 ± 3.4 mm for conventional placement and 15.1 ± 3.4 mm for the navigated procedure (P = 0.19). The inferior tilt showed no significant difference between the two methods (conventional 7.4 ± 5.2°, navigated 7.7 ± 4.9°, P = 0.63). The glenoid version in the axial plane showed significantly higher accuracy for the navigated procedure, with a mean deviation of 1.6 ±4.5° for the navigated procedure compared with 11.5 ± 6.5° for the conventional procedure(P = 0.004). Conclusion Accurate positioning of the glenoidal baseplate in the axial scapular plane can be improved using 3D C‐arm navigation for reversed shoulder arthroplasty. However, computer navigation may not improve the inferior tilt of the component or the position in the inferior glenoid to avoid scapular notching. Nevertheless, further studies are required to confirm these findings in the clinical setup. Copyright © 2013 John Wiley & Sons, Ltd.